Quantification of Hepcidin-related Iron Accumulation in the Rat Liver. (February 2016) - Böser, Preethne; Mordashova, Yulia; Maasland, Mark; Trommer, Isabel; Lorenz, Helga; Hafner, Mathias; Seemann, Dietmar; Mueller, Bernhard K.; Popp, Andreas
Hepcidin was originally detected as a liver peptide with antimicrobial activity and it functions as a central regulator in the systemic iron metabolism. Consequently suppression of hepcidin leads to iron accumulation in the liver. AbbVie developed a monoclonal antibody ([mAb]; repulsive guidance molecule [RGMa/c] mAb) that downregulates hepcidin expression by influencing the RGMc/bone morphogenetic protein (BMP)/neogenin receptor complex and causes iron deposition in the liver. In a dose range finding study with RGMa/c mAb, rats were treated with different dose levels for a total of 4 weekly doses. The results of this morphometric analysis in the liver showed that iron accumulation is not homogenous between liver lobes and the left lateral lobe was the most responsive lobe in the rat. Quantitative hepcidin messenger RNA analysis showed that the left lateral lobe was the most responsive lobe showing hepcidin downregulation with increasing antibody dose. In addition, the morphometric analysis had higher sensitivity than the chemical iron extraction and quantification using a colorimetric assay. In conclusion, the Prussian blue stain in combination with semi-quantitative and quantitative morphometric analysis is the most reliable method to demonstrate iron accumulation in the liver compared to direct measurement of iron in unfixed tissue using a colorimetric assay.